Aromatic Serenity: How Lavender Eases Stress and Anxiety - A Literature Review - Karolina Karoń; Łukasz Karoń; Anna Zygmunt; Wojciech Grabowski; Emilia Pedrycz; Grzegorz Drapała; Daria Pedrycz (Quality in Sport)
In today's fast-paced society, rising stress levels necessitate effective management strategies. While pharmacological treatments are common, their side effects have spurred interest in alternative therapies, particularly those rooted in natural remedies. Lavender (Lavandula angustifolia), long esteemed for its calming properties, has emerged as a promising non-pharmacological option. Historical use in herbal medicine for anxiety and stress-related disorders has inspired modern scientific research to explore its potential. This review synthesizes recent studies on lavender essential oil, examining its mechanisms—such as neurotransmitter modulation—and its effectiveness in diverse settings, from reducing stress among healthcare professionals to improving sleep quality. Despite promising results, limitations like small sample sizes and variability in application methods highlight the need for more rigorous research to establish lavender's efficacy and optimize its therapeutic use in stress management and mental health care.